Higher Education Quality Assurance and Accreditation and University Autonomy Implementation in Vietnam - Thi Thu Hien, Ta; Nhuan, Mai Trong; Huong, Nguyen Thi Thu; Phuong, Vu Minh; Uoc, Nguyen Cong (VNU Journal of Science: Education Research; Vol 38 No 2DO - 10.25073/2588-1159/vnuer.4660, 2022)
Along with the mechanism of quality assurance and accreditation that higher education system in Vietnam has been operating, university autonomy is a crucial factor in university governance, creating flexibility and dynamism for higher education institutions (HEIs), and increasing competitiveness among HEIs in the process of creating knowledge and leading the society to develop. The article clarifies the essence of university autonomy, the relationship between quality assurance, accreditation and university autonomy in Vietnam, thereby proposing solutions to promote autonomy for institutions to improve the efficiency and quality of higher education.